2011
DOI: 10.1029/2011jc007074
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of eddy generation in the western part of the Gulf of Lion

Abstract: [1] A realistic numerical model is used to investigate the generation process of anticyclonic eddies located in the western part of the Gulf of Lion. During 8 years of simulations from 2001 to 2008, 8 anticyclonic coastal eddies with a life duration longer than 15 days have been observed in the study area between July and early October. The formation process of eddies is linked to the wind stress curl in the area. Nonetheless a simpler criteria can be used examining the changes in the wind amplitude at a key c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…Hereafter, we adopt the terminology introduced by Hu et al . [] who defined long‐life eddies as the ones that last for at least 15 days. We have thoroughly studied year 2009 and two modeled long‐life anticyclonic eddies are identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hereafter, we adopt the terminology introduced by Hu et al . [] who defined long‐life eddies as the ones that last for at least 15 days. We have thoroughly studied year 2009 and two modeled long‐life anticyclonic eddies are identified.…”
Section: Resultsmentioning
confidence: 99%
“…These facts indicate that the generation process of the eddy A1 corresponds to the one described by Hu et al . [] for all long‐life eddies between 2001 and 2008.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on observations and modeling, previous studies have suggested various factors for eddy formation, such as the effect of bottom topography or irregular structure of the coastline (Kim, 2010;Zimmerman, 1981), spatial patterns in the wind field (Chavanne et al, 2002;Hu et al, 2011;Oey, 1996;Oey et al, 2001), shear flows (Shapiro et al, 1997) and the interplay of these factors with stratification and tidal forcing (Takeoka and Murao, 1993;Vethamony et al, 2005). Berman et al (2000) used a wind-driven numerical model to show the existence of a chain of cyclonic and anticyclonic eddies, semi-permanently residing along the main axis of the gulf.…”
Section: Introductionmentioning
confidence: 99%